Massive Myocardial Calcification and Normal Coronary Arteries - Barnard, Diane C. (1985)
We report a case of extensive myocardial calcification in a 50-year-old woman. It is rare when such cases are not associated with either metastatic deposition or infarction. However, this patient had a childhood illness of either rheumatic fever or some type of myocarditis, which most likely caused her extensive myocardial calcification.